Biological and Bioinspired Vesicles for Wound Healing: Insights, Advances and Challenges - Zhao Y; Zhang T; Zhao GL; Lu J; Zhang X; Lai Y; Chen Z; Ding X; Tai Z (International Journal of Nanomedicine)
Yingchao Zhao,1,* Tingrui Zhang,1,* Guan Lin Zhao,2,* Jiaye Lu,1 Xinyue Zhang,1 Yongxian Lai,1 Zhongjian Chen,1 Xiaofeng Ding,1 Zongguang Tai1 1Shanghai Skin Disease Hospital, School of Medicine, Tongji University, Shanghai, 200443, People’s Republic of China; 2Yangpu Hospital, School of Medicine, Tongji University, Shanghai, 200070, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaofeng Ding, Shanghai Skin Disease Hospital, School of Medicine, Tongji University, 1278 Baode Road, Shanghai, 200443, People’s Republic of China, Email dingxiaofeng1993@163.com Zongguang Tai, Shanghai Skin Disease Hospital, School of Medicine, Tongji University, 1278 Baode Road, Shanghai, 200443, People’s Republic of China, Email taizongguang@126.comAbstract: Millions of people suffer traumatic injuries and surgical procedures each year, making effective wound management very important. Benign wound repair is essential for structural and functional recovery of damaged tissues. Natural biological vesicles have emerged as attractive candidates for accelerating wound healing due to their endogenous nature and distinctive biological properties. However, obstacles such as low separation yields, potential safety concerns, and unsatisfactory production restrict their continuous application. In recent years, bioinspired materials and technologies have played an important role in the field of remodeling wound healing. Bioinspired vesicles function by effectively transporting therapeutic substances through mimicking the chemical and biological properties in nature, and can be modified and prepared through a variety of advanced techniques such as genetic engineering, chemical modification, and physical techniques, and are good substitutes for natural vesicles. Therefore, integrating bioinspired design into vesicles to promote wound healing can improve the curative effect while maintaining good safety, which helps to accelerate the clinical transformation of vesicles. This review discusses the latest progress, barriers to clinical transformation, and future development directions of biological and bioinspired vesicles for wound healing. Keywords: wound healing, biological vesicles, bioinspired vesicles, extracellular vesicles, preparation